A gendered outlook into the adoption of improved rice varieties in Madagascar. (2nd January 2022) - Mujawamariya, Gaudiose; Zenna, Negussie; Leonard, Lori; Tefy Andrianina, Irina; Ramiaramanana, Daniele
Abstract: This study investigates the household decision-making process toward adopting improved rice varieties. The mixed-method approach is applied to identify the influential factors and demonstrating the importance of considering gender aspects. The study was conducted in Madagascar Highlands (Vakinankaratra and Haute Matsiatra regions) with a sample of 164 male and female farmers. The quantitative models explored gendered differences for adoption, and the qualitative analysis elucidated farmers' preferences and factors that would limit or motivate adoption. Results show that at the time of the study, most farmers did not grow improved rice variety. No statistically significant gender differences in adoption levels were found; some explaining factors and preferences are gendered, pointing mainly to the labor implications of adoption. The qualitative analysis reveals similarities and sharp differences in preference attributes, abiotic stress resistance being the crucial factor in selecting varieties. Limiting factors include access to fertilizer, seeds, and finance; labor and time significantly constrain women. Technology development should be considered by applying a gender lens. For instance, male and female farmers must be involved in the initial stage of developing and deploying technology to deliver new varieties presenting traits suitable to the farmers' soil and other environmental conditions and their households' objectives. Technologies facilitating labor and time can reduce women's reluctance to adopt new varieties.